Koty to dranie. Obraz kota w wybranych słuchowiskach . - Łogożna-Wypych, Katarzyna (Zoophilologica. Polish Journal of Animal Studies, 2020)
Unpredictable and misunderstood, felines continue to mesmerize, attract and, at the same time, terrify human beings. In the sixteenth and seventeenth centuries cats were terrorizing humans as witches’ familiars, incarnation of Devil and messengers. Nowadays, they are able to convey the same sense of insecurity and menace with a sole appearance in a story. With a number of pets portrayed in radio dramas, cats are undoubtedly the most frequently depicted ones. Radio drama is an excellent medium to portray cats’ elusiveness and mysterious powers. Being the “blind medium” radio drama is able to convey the misconceptions and beliefs about cats most intuitively. In Koty to dranie by Jerzy Janicki the stereotypes about cats take control over man’s common sense, the thoughtless cruelty towards them being depicted as a sudden and surprising action. Grochola in Kot mi schudł offers an interesting study on much too common ill treatment of felines, the worthlessness of cats in human eyes, and, on the other hand, the ability of cats to change human lives, loneliness being the main focus of the radio drama. Felines tend to be quite persuasive, thus it is the cat, more often than any other animal, that not only is able to change the track of events in the plot, but also provides a particular bridge between contrasting worlds or conventions. Cat is never just a cat. It is the beginning, the main body, and the conclusion in the invisible world of radio drama with all archetypical notions that they may possess.